Lei geral das micro e pequenas empresas: o tratamento diferenciado aos pequenos negócios nas licitações públicas de osasco - Ulliana, Marcelo Rodrigues [UNIFESP] (2015)
The Micro and Small Enterprises (MSEs) have essential role in the socio-economic context of the country, both for its high representation in number of companies and geographical reach, as for its capacity to generate employment and income. However, small businesses still have a high mortality rate due to numerous factors, including the difficulty in competing with medium and large companies. In this way, public policies that provide to the small businesses differentiated legal treatment, seeking to encourage them are essential so that they can act in a more egalitarian condition in a market as competitive as the current one. In Brazil, the different legal treatment, simplified and favored to MSEs is constitutionally guaranteed, and is already regulated since 2006 by Complementary Law No. 123, called the National Statute of Micro and Small Companies and has been regulated by several Brazilians municipalities. One of the important points is the grant by these standards differentiated and privileged legal treatment to MSEs in Public Bids of the Direct and Indirect Administration aimed at promoting economic and social development at the municipal and regional levels, as well as the expansion of public policy efficiency. The objective of this study was to investigate this as differentiated and privileged treatment in law legally granted to MSEs occurs in Public Procurement of Osasco, and the level of participation by the small local companies in the bids. Although the results of this study cannot be considered conclusive, they provide valuable evidence of the low participation of MSE's in the bids of Osasco Prefecure, especially when compared with other counties with some similar features that have achieved greater participation of MSE's in their bids.